A novel phosphonic acid functional polythiophene fluorescent sensor for Ca2+ and its live cell imaging. Issue 39 (24th September 2019) - Yang, Ting; Hu, Zhiru; Liu, Jilin; Zhang, Zhiquan; Feng, Guodong
Abstract : Calcium ions are indispensable to various physiological activities of the body, so the detection of calcium ions is very important. Abstract : Calcium ions are indispensable to various physiological activities of the body, so the detection of calcium ions is very important. In this work, a new water-soluble polythiophene derivative poly((thiophene-3, 4-diylbis(oxy))bis(propane-3, 1-diyl))bis(phosphonic acid) (PT-PHO) was designed and synthesized via oxidative polymerization with FeCl3 . The polymer containing phosphonic acid groups could be used as a "turn off" fluorescent sensor for Ca 2+ detection. Under optimal conditions, PT-PHO exhibits high selectivity and sensitivity to detect Ca 2+ among metal ions. The fluorescence intensity of PT-PHO shows a linear response toward Ca 2+ in the range of 0.05–50 μmol L −1 with a limit of detection (LOD) of 44 nmol L −1 . In addition, PT-PHO has low toxicity and good biocompatibility. Thus, it could be used for imaging lysosomes in cells and detecting intracellular calcium ions.